The Economic and Social Conditions of the Physical Activity of People who are 50+ in the Light of Research - Sikora , Jan; Wartecka-Ważyńska, Agnieszka (Studia Oeconomica Posnaniensia, 2018)
The aim of the study was to present selected economic and social factors of the physical activity of people aged 50+. The achievement of the research goal was supported by the results of questionnaire surveys carried out in institutions competent for the older generations in Poznań (N = 227) and relevant literature on the subject. The empirical and literature analysis confirmed that people aged 50+ have enough time off in which they can take various forms of physical activity. The obtained research results indicated that the respondents more often practiced passive than active physical activity, which was connected with their material situation. Passive forms of this activity are less costly and also the equipment used for this activity is much cheaper. However, the respondents noted the health and social benefits of active forms of recreation. However, their implementation was not possible for everyone, mainly due to the economic situation. The completed studies have not only cognitive value, but also application in the field of the social policy of the elderly.